Pengaruh Pertumbuhan Ekonomi, Pendidikan Dan Kesehatan Terhadap Indeks Pembangunan Manusia Di Provinsi Sumatera Utara - Hasibuan, Siti Rama; Harahap, Isnaini; Tambunan, Khairina (Universitas Labuhanbatu, 2023)
This study aims to determine and analyze the effect of economic growth, education and health on the Human Development Index in North Sumatra province in 2017-2021.The population in this study is the annual report of economic growth, education that is proxied with data on average length of school, health that is proxied with data on life expectancy, and the Human Development Index in North Sumatra province for the period 2017-2021. The sample of this study amounted to 165 with time series data for 5 years and cross section data amounted to 33 districts/cities of North Sumatra province. The Data used in this study are secondary data and sampling techniques performed by saturated sample Method.Analytical techniques used are descriptive statistical analysis test, classical assumptions, multiple linear regression and hypothesis testing.Partial results showed that economic growth does not have a positive and significant effect on the Human Development Index, education has a positive and significant effect on the Human Development Index, and health has a positive and significant effect on the Human Development Index in North Sumatra province.The results of the study simultaneously showed that economic growth, education and health have a positive and significant effect on the Human Development Index in North Sumatra province.